Complementary Therapies in Reducing of Emesis Gravidarum - Tri Restu Handayani (Science Midwifery, 2022)
Nausea and vomiting in early pregnancy are very common, affecting approximately 80% of the pregnancies, hyperemesis gravidarum is a severe form affecting 0.3–1.0% of the pregnanciesEmesis gravidarum can be treated using complementary therapies such as ginger and lemon. Ginger and lemon have a pharmacological function as an antimyetic. Objective: to determine the effect of ginger water and lemon inhalation in reducing emesis gravidarum. Method : pretest-posttest experiment with control group design. The experimental group was given ginger water, the control group was given lemon inhalation. The study was conducted at the Nagaswidak Health Center in June - July 2022. The sample consisted of 60 pregnant women who met the inclusion criteria using purposive sampling technique. Data were analyzed using paired sample t test and non-parametric Mann Whitney test. The results of the paired sample t test of the experimental group obtained t : 4.726 p value 0.004 (p < 0.05) and the control group obtained t : 4.878 p value 0.005 (p < 0.05). The non-parametric Mann Whitney test obtained p value of 0.004 (p < 0.05). There was a change in the scale of nausea and vomiting in the experimental group and the control group before and after the intervention.